A new species of Teleogryllus (Teleogryllus) Chopard, 1961 from Yunnan, China (Orthoptera: Gryllidae: Gryllinae) - Liu, Yun-Fei; Shen, Chu-Ze; Xu, Yue; Chen, Guang-Yu; He, Zhu-Qing (Zootaxa, 2018)
There are six species of genus Teleogryllus Chopard, 1961 recorded from China prior to this study. They belong to either subgenus Macroteleogryllus or subgenus Brachyteleogryllus. We describe a new species, Teleogryllus (Teleogryllus) albipalpus He sp. nov. belonging to subgenus Teleogryllus from Yunnan, China. The morphology of adults and nymphs in different instars, songs and COI gene are provided. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).